Representation of Cultural Values in Balochi Classical Poetry - Yaseen, Muhammad; Hakeem, Tahir; Saba, Sadiq (Pakistan Languages and Humanities Review, 2024)
The study explores classical Balochi poetry from the 16th century onwards, tracing its evolution through different eras and highlighting key themes of bravery, love, and societal norms. The research methodology employs qualitative analysis, focusing on classical poetries from renowned Balochi literature works. Thematic coding is utilized to categorize and analyze recurring cultural themes, offering a deeper understanding of how poets represented Baloch cultural identity. The paper explores cultural elements such as the protection of "bāhoat," adherence to vows, the tradition of revenge ("Beirgiri"), and the social practice of "Shigaan" or taunting. The intricate analysis sheds light on the multifaceted nature of Balochi classical poetry, emphasizing its role as a preserver of cultural identity. The paper concludes by suggesting the need for further research to unearth hidden nuances within the poetic tradition and explore contemporary resonances of Balochi classical poetry in the context of cultural preservation and identity assertion.